2021
DOI: 10.1111/joop.12345
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and positive activities at work: Intervention effects on motivation‐related constructs, sleep quality, and fatigue

Abstract: Positive psychology research is increasingly being transferred to organizational contexts, and organizations are increasingly striving for healthier and more motivated employees. In this study, a three‐week self‐instructed online intervention which combines positive activities and mindfulness was developed and evaluated using a randomized‐controlled group design with employees. All exercises could be easily integrated into the daily working routine. The intervention is based on broaden‐and‐build theory, the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“… #2492 Mindfulness as a cognitive–emotional segmentation strategy: An intervention promoting work–life balance Michel et al 2014 Journal of Occupational and Organizational Psychology Germany Design and evaluate an intervention teaching mindfulness as a cognitive–emotional segmentation strategy to promote work–life balance. #3747 Mindfulness and positive activities at work: Intervention effects on motivation-related constructs, sleep quality, and fatigue Michel et al 2021 Journal of Occupational and Organizational Psychology Germany In this study, a three-week self-instructed online intervention which combines positive activities and mindfulness was developed and evaluated using a randomized-controlled group design with employees. All exercises could be easily integrated into the daily working routine.…”
Section: Resultsmentioning
confidence: 99%
“… #2492 Mindfulness as a cognitive–emotional segmentation strategy: An intervention promoting work–life balance Michel et al 2014 Journal of Occupational and Organizational Psychology Germany Design and evaluate an intervention teaching mindfulness as a cognitive–emotional segmentation strategy to promote work–life balance. #3747 Mindfulness and positive activities at work: Intervention effects on motivation-related constructs, sleep quality, and fatigue Michel et al 2021 Journal of Occupational and Organizational Psychology Germany In this study, a three-week self-instructed online intervention which combines positive activities and mindfulness was developed and evaluated using a randomized-controlled group design with employees. All exercises could be easily integrated into the daily working routine.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying supportive resources to enhance coping skills and reduce psychological distress on an individual level may be beneficial as systems work to implement meaningful change. For example, Michel and colleagues (2021) developed and implemented a 3-week mindfulness intervention and found that participants experienced reduced impact of work stress on family roles and more satisfaction with work–life balance compared to control group participants. While these interventions have not been evaluated with women in STEM or academia, it is possible that interventions targeting internal psychological skills have potential to reduce levels of distress experienced by women like those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Social interactions can be a source of emotional energy since positive social experiences promote feelings of emotional energy ( Michel et al, 2021 ). The concept of energy may overlap with the concept of well-being ( Diener, 1984 ), as people high in energy may also be high in well-being ( Ryan and Frederick, 1997 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%